Self-generated morphology in lagoon reefs - Blakeway,David; Hamblin,Michael G (PeerJ PrePrints, 2014)
The shapes and forms of coral reefs are generally attributed to external controls such as substrate topography or hydrodynamic influences. Little is known about inherent reef morphology in the absence of external control. Here we use reef growth simulations, based on observations in the cellular reefs of Western Australia’s Houtman Abrolhos Islands, to show that reef morphology is fundamentally determined by the mechanical behaviour of the reef-building organisms themselves—specifically their tendency to either remain in place or to collapse. A spectrum of realistic reef forms can be generated by varying a single parameter representing this characteristic. Reef-building organisms that tend to remain in place, such as massive and encrusting corals or coralline algae, produce nodular reefs, whereas those that tend to collapse, such as branching Acropora, produce cellular reefs. Inherent reef growth forms are best expressed in sheltered lagoons. The purest forms arise where a single type of reef builder prevails, as in the cellular reefs of the Abrolhos. In these cases reef morphology can be considered a phenotype of the predominant reef building organism.
Keywords: Acropora; automaton; cellular; coral; emergence; geomorphology; Holocene; Houtman Abrolhos; reticulate; self-organised